Trace elements in the spinal cord and other tissues in motor neuron disease. Issue 2 (February 1986) - Mitchell, J D; East, B W; Harris, I A; Prescott, R J; Pentland, B
Abstract : Trace elements were estimated in the spinal cord, liver and bone of five patients dying of motor neuron disease and five control subjects dying of non-neurological disease. The content of selenium in cord and liver and the cord manganese level were significantly increased in the motor neuron disease patients. These findings are discussed in terms of the possible aetiology of motor neuron disease.